TAX PLANNING SEBAGAI STRATEGI EFISIENSI PPH BADAN PADA PT YUPI INDO JELLY GUM TBK - Cahyaningtyas, Rahmayanti; Adi Prawira, Ida Farida; Kustiawan, Memen (Journal of Financial and Tax, 2026)
This study aims to analyze the implementation of tax planning as an effort to improve Corporate Income Tax efficiency at PT Yupi Indo Jelly Gum Tbk. This research employs a descriptive qualitative method with a case study approach, utilizing secondary data from the Annual Financial Reports for the fiscal years 2023 and 2024. The analysis focuses on the fiscal reconciliation of entertainment expenses, donations, and financial expense, which significantly contribute to positive fiscal corrections. The results indicate that prior to tax planning, the company bore a higher tax expense due to expenses classified as non-deductible. By implementing tax strategies, specifically create of a Nominative List for entertainment expenses, aligning donations with the criteria of Government Regulation No. 93 of 2010, and proving the business purpose of loan funds (tracing) to satisfy the 3M principle, these expenses were successfully reclassified as deductible expenses. The simulation results demonstrate that these strategies generated tax savings of IDR 244,769,140 in 2023 and IDR 790,359,240 in 2024. This study concludes that legal tax planning is effective in optimizing tax liabilities while maintaining compliance with applicable tax regulations.